(untitled) (Anclajes, 2019)
Queer / Cuir and Crip refer to non-normative bodies, to stigmatized identities. In this sense, from an intersectional framework they advocate establishing alliances between the differences that exclude and discriminate, which helps us to deconstruct those elements, traits and characteristics that make up a normative body, as opposed to the one that is not.